Children's Physical Activity and On-Task Behavior Following Active Academic Lessons: 2017 National Association for Kinesiology in Higher Education Hally Beth Poindexter Young Scholar Address. Issue 2 (3rd April 2017) - Goh, Tan Leng
ABSTRACT: Sitting for extended periods of time is detrimental to children's physical health and may cause off-task behavior in the classroom. The purpose of this study was to examine the effect of a classroom physical activity (PA) program, TAKE 10!®, on children's PA and on-task behavior. Participants in the program included 137 children from six classes (third to fifth grades) in one ethnically diverse elementary school in the Southwestern United States. Classroom teachers implemented 10-minute bouts of active academic TAKE 10!® lessons for 12 weeks (four weeks baseline and eight weeks intervention). PA was measured using pedometers and on-task behavior was measured using systematic observation in the classrooms. Children's step counts increased significantly ( p < 0.05) by 853 from baseline to end-intervention. There was also significant ( p < 0.05) improvement in on-task behavior of 5.5%. Active academic lessons were effective in increasing children's in-school PA and on-task behavior in the classroom.